Odpowiedzi

2009-11-03T17:23:38+01:00
-3¾ × (-3 3/5) × (-0,625) × (-1,4)=
-2 2/3 × (-1,5) × (-3 1/3) ×(-0,6) × (-1) =
- 8/3 × (-3,14) × (-1 5/7) × (-1) × [-(-14)] =
=5554
2009-11-03T17:39:45+01:00
2009-11-03T18:00:13+01:00
-3¾ × (-3 3/5) × (-0,625) × (-1,4)= -3,75 x (- 3,6) x (-0,625) x (-1,4) = 12,6 x (-0,625) x (-1,4) = -7,875 x (-1,4) = 11,025
-2⅔ × (-1,5) × (-3⅓) ×(-0,6) × (-1) = - 2⅔ x (-1½) x (-3⅓) x (-⅗) x (-1) = 8/3 x (-3/2) x (-10/3) x (-⅗) x (-1) = -24/6 x (-10/3) x (- ⅗) x (-1) = 40/3 (po skróceniu) x (-⅗) x (-1) = -8/1 x (-1) = 8/1 = 8
- 8/3 × (-3,14) × (-1 5/7) × (-1) × [-(-14)] = -8/3 x (-3 14/100) x ( - 1 5/7) x (-1) x 14 = 628/75 x (- 1 5/7) x (-1) x 14 = - 2512/175 x (-1) x 14 = 2512/175 x 14 = 5024/25 = 200 24/25